Le couvent de Beaujeu : une approche du tiers-ordre franciscain à travers l’étude d’un « petit » couvent - Matthieu Cathalan (Chrétiens et Sociétés, 2022)
The study of the franciscan third order, also known as “Picpus” has been widely neglected among the regular orders of beggars in France. A few studies, mostly monographs on the scale of a single convent constitute most of the scientific literature dedicated to this order, who suffers in addition from a negative reputation, assigned in the 18th century and repeated until today, without being fundamentally called into question.This article proposes an approach of the third order through a monography of Beaujeu convent, centered around the relations between the regular clergy and the local population (including both laymen and secular clergy), relying on the exhaustive study of civil trials involving Beaujeu convent over it’s two-centuries long existence, from 1627 to 1790.The study of these trials in relation to the convent relations with civilian population are tightly related to the question of the material administration of the convent, but also to disputes related to the land properties of the convent, to the delimitation of the inclosure and the sharing of the public domain. We attempted to highlight the struggles, accommodations and concessions between the convent monks and the outer world. Aiming to nuance the simplistic representation of the quarrelling Picpus monk, we tried to demonstrate that the civilian trials involving the convent are not simply the evidence of an unsurpassable dispute, but rather an appropriated terrain for the finding of an agreement, a modus vivendi between the stakeholders.